Lipolysis in probiotic and synbiotic cheese: the influence of probiotic bacteria, prebiotic compounds and ripening time on free fatty acid profiles - Rodrigues, Dina (2019)
The influence of probiotic bacteria (Lactobacillus casei-01, Bifidobacterium lactis B94), prebiotic compounds (FOS and inulin) and ripening time (0–60 days) on the free fatty acid (FFA) profile of cheese, with special emphasis on the conjugated linoleic acid (CLA) content, was investigated. After 60 days of ripening, 109–1010 cfu g−1 cheese were recorded in both probiotic and synbiotic cheeses, despite harsh conditions of low pH values (4.1–5.1) and low moisture content (<30%, w/w). Increases in total FFA and CLA were observed throughout the ripening period, especially in synbiotic cheeses containing FOS and inulin (50:50) inoculated with B. lactis B94. The addition of FOS alone or combined with inulin did not significantly affect probiotic strain growth and viability during the ripening period; however, the advantage of the addition of prebiotic compounds in probiotic cheese manufacture is that it may allow the production of cheeses with improved performance as far as functional CLA compounds are concerned, as well as an improved nutritional quality reflected in a lower atherogenicity index.